El verano es divertido! - Moon, Walt K.; Granat, Annette (Minneapolis, MN : Lerner, 2017)
Simple text and photographs engage young readers in learning about the changes and adaptations summer brings.
English title: Summer is fun!
Includes bibliographical references and index.
P-1.
4-6.
Keywords: Summer -- Juvenile literature; Seasons -- Juvenile literature